What do we know about fashion advertising? A review of the literature and suggested research directions. Issue 1 (2nd January 2017) - Taylor, Charles R.; Costello, John P.
ABSTRACT: This paper's aim is to provide a comprehensive review of the literature on fashion advertising. Toward this end, the paper describes major theoretical perspectives that have been used in fashion advertising research; discusses major findings that the cumulative body of research has produced in key sub-areas of fashion advertising research; and provides directions for future research. Key sub-areas of the field which are discussed include what factors lead to effective advertisements; how different types of models affect consumers and influence the effectiveness of ads; how consumers can be segmented potentially across nations; how social media advertising can be used to produce positive marketing outcomes; and how controversial fashion advertising impacts consumers. Future areas of research in the area of fashion advertising are identified and explored.